2021
DOI: 10.1051/0004-6361/202140611
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic field inference in active region coronal loops using coronal rain clumps

Abstract: Aims. We aim to infer information about the magnetic field in the low solar corona from coronal rain clumps using high-resolution spectropolarimetric observations in the Ca II 8542 Å line obtained with the Swedish 1 m Solar Telescope. Methods. The weak-field approximation (WFA) provides a simple tool to obtain the line-of-sight component of the magnetic field from spectropolarimetric observations. We adapted a method developed in a previous paper in order to assess the different conditions that must be satisfi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
(49 reference statements)
0
10
1
Order By: Relevance
“…This quantity can be used to estimate the amplitudes from transverse MHD waves (Pant and Doorsselaere, 2020), and therefore their energy flux and potential role in coronal heating. As stated in section 2.2.3, non-thermal line broadening can vary significantly depending on the event, with loops showing average values between 5-10 km s −1 only (Antolin et al, 2015;Kriginsky et al, 2021) while others show values of 8-16 km s −1 (with a tail up to 22 km s −1 ), that is, on the same order or larger than the thermal component Froment et al (2020), see Figure 10. It is interesting to note that the 15-20 km s −1 range is common in active region loops with temperatures between 1 MK and 5 MK (Chae et al, 1998;Hara and Ichimoto, 1999;Brooks and Warren, 2016;Testa et al, 2016), and also with that obtained from models based on either MHD waves (Shi et al, 2021) or field-line braiding (Pontin et al, 2020), which suggests that the same level of turbulence can be found in loops with or without TNE.…”
Section: Implication For the Energetics Variability And Morphology Of...mentioning
confidence: 81%
See 3 more Smart Citations
“…This quantity can be used to estimate the amplitudes from transverse MHD waves (Pant and Doorsselaere, 2020), and therefore their energy flux and potential role in coronal heating. As stated in section 2.2.3, non-thermal line broadening can vary significantly depending on the event, with loops showing average values between 5-10 km s −1 only (Antolin et al, 2015;Kriginsky et al, 2021) while others show values of 8-16 km s −1 (with a tail up to 22 km s −1 ), that is, on the same order or larger than the thermal component Froment et al (2020), see Figure 10. It is interesting to note that the 15-20 km s −1 range is common in active region loops with temperatures between 1 MK and 5 MK (Chae et al, 1998;Hara and Ichimoto, 1999;Brooks and Warren, 2016;Testa et al, 2016), and also with that obtained from models based on either MHD waves (Shi et al, 2021) or field-line braiding (Pontin et al, 2020), which suggests that the same level of turbulence can be found in loops with or without TNE.…”
Section: Implication For the Energetics Variability And Morphology Of...mentioning
confidence: 81%
“…While the WFA provides the LOS component of the field, the total magnitude can be inferred from the rain's trajectory, which in turn can be known from the ratio between the POS and Doppler (LOS) velocity component. Using this, Kriginsky et al (2021) infer total field values of 500 G (with minima/maxima of 200/1,000 G) at heights of ≈ 10 Mm above the limb (probably, 15-20 Mm heights or so above the surface) in an active region (see Figure 18), consistent with the measurements of Schad et al (2016). These coronal magnetic field measurements are striking since they are a factor of 10 larger than usually assumed coronal magnetic field values in the corona.…”
Section: Implication For the Energetics Variability And Morphology Of...mentioning
confidence: 99%
See 2 more Smart Citations
“…τ is always exceptionally large for n 1 > 10 11 cm −3 . This means that the RTI is likely to form under usual coronal rain conditions, but only for weak magnetic fields that may not be expected in active regions (Nakariakov & Ofman 2001;Kriginsky et al 2021). This aligns with the work by Moschou et al (2015) and Xia et al (2017), who have simulated coronal condensation that shows the formation of RTI using weak magnetic fields of less than 10 G at the apex of the loop.…”
Section: Rtimentioning
confidence: 99%